Utilization of pineapple (Ananas comosus) plant stem as starch and lignocellulose feedstock for biobased products - Abd-Aziz, Suraini (2022)
Pineapple plant (Ananas comosus) is one of the largest productions in Asia and its increasing production has generated a huge amount of pineapple wastes. Productions of value-added products using pineapple plant wastes are widely done, but little effort has been studied for pineapple plant stem. Pineapple plant stem is rich in hemicellulose and cellulose, which can be used in the production of fermentation products. Despite the high cellulosic content, little effort has been done to utilise pineapple plants stems. Pineapple plants stems have become a significant agricultural waste as this renewable waste resource can be a good source of starch. Starch is the most abundant biomolecule on earth after cellulose and the major carbohydrate reserve in plants. Demand for native starches increased globally as it can minimise the use of chemically modified starches. This study aimed to utilize starch and lignocellulose from pineapple plant stem hydrolysates through microbial fermentation as feed stock for biobased products. The composition of pineapple plant stem, mostly consists of starch and lignocellulosic materials plus other types of pectic substances, makes it possible to produce amino acids from pineapple plant stem by employing the direct fermentation process which can be applied in the animal feed industry. Since the demand for feed-grade amino acids is increasing, especially in the production of methionine and lysine, thus, study should be done on utilizing agricultural waste to produce amino acids through microbial fermentation in place of chemical synthesis. Pineapple plant stem showed high starch content of 77.78%. Lignocellulosic composition of pineapple plant stem, consisted of 46.15% hemicellulose, 31.86% cellulose and 18.60% lignin. The hydrolysates obtained were used in the fermentation to produce methionine and lysine. It was observed that higher methionine and lysine production were produced from starch-based hydrolysis (40.25 mg/L and 0.97 g/L, respectively) as compared to cellulosic-based saccharification (37.31 mg/L and 0.84 g/L, respectively) of pineapple plant stem. The amino acids produced from the agricultural biomass, thus, throw a light on the valorisation of pineapple plant stem for value-added products.